Revitalization Of Islamic Education: A Model Of Supervision And Guidance Of Human Resources Oriented Towards Increasing Public Interest In Islamic Educational Institutions - Jaswadi; Binti Maunah; Imam Junaris; Moch. Rikza Alkhubra Abdul Jabbar; Anta Gusnanda (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This research is motivated by the urgency of human resource (HR) supervision and development in Islamic educational institutions, considering the low level of public interest in actively participating in the educational programs being conducted. The main objective of this research is to develop and analyze an effective model of HR supervision and development, with the hope of encouraging public interest in Islamic educational institutions. The research method used in this study is library research, data obtained from literature related to HR management and public interest in Islamic education, analyzed through a systematic review with validity tested through triangulation of sources and expert opinions . The results indicate that a comprehensive HR needs analysis, recruitment of qualified educators, and supervision and performance evaluation involving the active participation of parents of students, contribute significantly to improving the quality of teaching and public interest. HR needs analysis plays a role in identifying required competencies, recruitment of qualified educators has a positive impact on improving student learning outcomes, and supervision and performance evaluation involving parents of students creates transparency and strengthens the image of educational institutions. In addition, active community involvement in workshops and seminars, as well as improving the image of institutions through effective social and promotional activities, have also proven effective in attracting public attention. This study concludes that the implementation of an effective model of human resource supervision and development can create a more attractive and relevant educational environment, as well as increase public interest in Islamic education.